1996
DOI: 10.1016/s0092-8674(00)81388-4
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Embryonic Hematopoiesis andLethal Hemorrhages in Mouse Embryos Heterozygousfor a Knocked-In Leukemia Gene CBFB–MYH11

Abstract: The fusion oncogene CBFB-MYH11 is generated by a chromosome 16 inversion in human acute myeloid leukemia subtype M4Eo. Mouse embryonic stem (ES) cells heterozygous for this oncogene were generated by inserting part of the human MYH11 cDNA into the mouse Cbfb gene through homologous recombination (knock-in). Chimeric mice were leukemia free, but the ES cells with the knocked-in Cbfb-MYH11 gene did not contribute to their hematopoietic tissues. Mouse embryos heterozygous for Cbfb-MYH11 lacked definitive hematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
230
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(245 citation statements)
references
References 38 publications
11
230
1
2
Order By: Relevance
“…Consistent with the importance of CBF for the growth and maturation of immature blood cells, gene rearrangements involving CBF subunits are commonly found in AML (as recently reviewed, Liu et al, 1995;Nucifora and Rowley, 1995) and in pediatric B-lineage ALL (Golub et al, 1995;Romana et al, 1995). Remarkably, mice derived from ES cells heterozygous for CBFb-SMMHC at the CBFb locus or for AML1-ETO at the AML1 locus, displayed the same phenotypes as did CBFb or AML1 null mice, including lack of de®nitive hematopoiesis (Castilla et al, 1996;Okuda et al, 1996b;Yergeau et al, 1997). Also, AML1-ETO interfered with transactivation by AML1 Frank et al, 1995), and CBFb-SMMHC inhibited CBF DNA-binding in vitro and in NIH3T3 cells .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Consistent with the importance of CBF for the growth and maturation of immature blood cells, gene rearrangements involving CBF subunits are commonly found in AML (as recently reviewed, Liu et al, 1995;Nucifora and Rowley, 1995) and in pediatric B-lineage ALL (Golub et al, 1995;Romana et al, 1995). Remarkably, mice derived from ES cells heterozygous for CBFb-SMMHC at the CBFb locus or for AML1-ETO at the AML1 locus, displayed the same phenotypes as did CBFb or AML1 null mice, including lack of de®nitive hematopoiesis (Castilla et al, 1996;Okuda et al, 1996b;Yergeau et al, 1997). Also, AML1-ETO interfered with transactivation by AML1 Frank et al, 1995), and CBFb-SMMHC inhibited CBF DNA-binding in vitro and in NIH3T3 cells .…”
Section: Discussionmentioning
confidence: 96%
“…Mice in which the CBFb-SMMHC or AML1-ETO cDNAs had been`knocked-in' to their normal loci failed to develop de®nitive hematopoiesis and died in utero (Castilla et al, 1996;Okuda et al, 1996b;Yergeau et al, 1997). These phenotypes are identical to that of AML1 and CBFb null mice, providing additional evidence that these oncoproteins act by inhibiting CBF functions.…”
Section: Introductionmentioning
confidence: 89%
“…The CBFb subunit is altered in the inv(16) chromosomal abnormality, to form a CBFb-MYH11 fusion protein (Liu et al, 1993). Both AML1/ETO (Okuda et al, 1998;Yergeau et al, 1997) and CBFb-MYH11 (Castilla et al, 1996) knock-in mice fail to develop de®nitive hematopoiesis, suggesting that the fusion proteins could account for the block in di erentiation characteristic of AML. However, because of the lethal phenotype of the knock-in mice, the role of the fusion proteins in leukemogenesis has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The a subunit, with DNA binding properties, contains a region of homology with the runt gene of Drosophila (Daga et al, 1992) and the b subunit stabilizes the binding of the a subunit to DNA. Recent work has demonstrated that both subunits are essential for a correct hematopoiesis (Okuda et al, 1996;Wang et al, 1996a,b;Castilla et al, 1996;Sasaki et al, 1996;Yergeau et al, 1997;Niki et al, 1997) and that their disruption may be crucial for leukemogenesis. Other genes are found involved together with the CBF genes in di erent leukemia subtypes.…”
Section: Introductionmentioning
confidence: 99%